2004
DOI: 10.1038/sj.eye.6701421
|View full text |Cite
|
Sign up to set email alerts
|

Screening for visual impairment in elderly patients with hip fracture: validating a simple bedside test

Abstract: Aims 1. To assess the prevalence of visual impairment in those patients who sustain proximal hip fracture after a simple fall. 2. To test the validity of a simple screening test to identify patients with visual impairment. Methods Patients on the orthopaedic rehabilitation ward recuperating from proximal hip fracture were recruited. The nurse screener and examining Ophthalmologist independently assessed the patients' distance visual acuity and visual field to confrontation. In addition, the nurse screener asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 24 publications
(33 reference statements)
0
27
0
1
Order By: Relevance
“…Squirrell et al, studied a cohort of 89 elderly patients with hip fractures and found significant visual impairment in 58% [29]. Since, visual impairment has emerged as an important factor contributing to the fracture; it underscores the need for appropriate visual assessment in this age group and early correction of visual defects [12].…”
Section: Visual Impairmentmentioning
confidence: 99%
“…Squirrell et al, studied a cohort of 89 elderly patients with hip fractures and found significant visual impairment in 58% [29]. Since, visual impairment has emerged as an important factor contributing to the fracture; it underscores the need for appropriate visual assessment in this age group and early correction of visual defects [12].…”
Section: Visual Impairmentmentioning
confidence: 99%
“…36 Persons whose visual acuity screening was positive for visual impairment were referred to an eye care provider with a compliance rate of 95%. 10 Those persons who truly had visual impairment received treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the prevalence of hip fracture was significantly linked to vision impairment in older adults [8]. …”
Section: Introductionmentioning
confidence: 99%